2019
DOI: 10.1016/j.anpede.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Criteria heterogeneity in the diagnosis of acute bronchiolitis in Spain

Abstract: Introduction: Acute viral bronchiolitis (AB) is one of the most common respiratory diseases in infants. However, diagnostic criteria for AB are heterogeneous and not very well known. Objective: To identify the diagnostic criteria for AB used by experts and clinical paediatricians in Spain. Methods: Delphi study with Spanish AB experts, looking for the points of agreement about AB diagnosis. A subsequent cross-sectional study was conducted by means of an online questionnaire addressed to all Spanish paediatrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…The causative virus and the inclusion or exclusion of infants with previous presentations and/or various comorbidities are additional sources of variability [18]. In a recent survey of Spanish pediatricians, it was determined that the adherence to diagnostic criteria for viral bronchiolitis is heterogeneous, with high agreement on issues such as being the first episode of respiratory distress and the usefulness of virus identification in making a diagnosis, but poor agreement on other important issues such as the maximum age for diagnosis [19]. Notably, although there is overall consensus that the term viral bronchiolitis must be used only to describe the first/ single episode of viral LRTI in infants, a recent study found that >60% of bronchiolitis cases requiring hospitalization are really recurrent wheezing cases [20].…”
Section: Shortcomings Of Grouping Diverse Respiratory Syndromes As a Single Conditionmentioning
confidence: 99%
“…The causative virus and the inclusion or exclusion of infants with previous presentations and/or various comorbidities are additional sources of variability [18]. In a recent survey of Spanish pediatricians, it was determined that the adherence to diagnostic criteria for viral bronchiolitis is heterogeneous, with high agreement on issues such as being the first episode of respiratory distress and the usefulness of virus identification in making a diagnosis, but poor agreement on other important issues such as the maximum age for diagnosis [19]. Notably, although there is overall consensus that the term viral bronchiolitis must be used only to describe the first/ single episode of viral LRTI in infants, a recent study found that >60% of bronchiolitis cases requiring hospitalization are really recurrent wheezing cases [20].…”
Section: Shortcomings Of Grouping Diverse Respiratory Syndromes As a Single Conditionmentioning
confidence: 99%
“…El primer paso para realizar es una buena historia clínica y ahondar en la anamnesis, de ella debemos rescatar factores de riesgo que puedan estar relacionados a un desarrollo más grave de la enfermedad. Entre ellos, debemos preguntar lo siguiente: edad (más grave en menores de 6 semanas), si es nacido prematuro, alguna patología de antecedente personal, tiempo de evolución, si hay personas que fuman en el entorno o cerca al niño, si hubo lactancia materna o no, si el niño tubo bajo peso al nacer (menor a 2500 gr) y estatus socioeconómico (por hacinamiento y pobreza) (47).…”
Section: Diagnósticounclassified
“…Es adecuado apoyarse en una escala que objetive la severidad del cuadro, idealmente debería usarse una escala que tenga como parámetros clínicos: frecuencia respiratoria y cardiaca, y saturación de oxígeno. La escala más usada y propuesta es la de Wood-Downes (47).…”
Section: Diagnósticounclassified